2023
DOI: 10.3390/diagnostics13091611
|View full text |Cite
|
Sign up to set email alerts
|

The GRPR Antagonist [99mTc]Tc-maSSS-PEG2-RM26 towards Phase I Clinical Trial: Kit Preparation, Characterization and Toxicity

Abstract: Gastrin-releasing peptide receptors (GRPRs) are overexpressed in the majority of primary prostate tumors and in prostatic lymph node and bone metastases. Several GRPR antagonists were developed for SPECT and PET imaging of prostate cancer. We previously reported a preclinical evaluation of the GRPR antagonist [99mTc]Tc-maSSS-PEG2-RM26 (based on [D-Phe6, Sta13, Leu14-NH2]BBN(6-14)) which bound to GRPR with high affinity and had a favorable biodistribution profile in tumor-bearing animal models. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Gastrin-releasing peptide receptor (GRPR), a subtype of the bombesin (BBN) G protein-coupled receptor family, is overexpressed in prostate cancer, particularly in low-grade and smaller tumors [ 16 , 29 ]. RM2 is one of the extensively applied synthetic GRPR antagonists.…”
Section: Diagnostic Role Of Grpr In Pcamentioning
confidence: 99%
See 3 more Smart Citations
“…Gastrin-releasing peptide receptor (GRPR), a subtype of the bombesin (BBN) G protein-coupled receptor family, is overexpressed in prostate cancer, particularly in low-grade and smaller tumors [ 16 , 29 ]. RM2 is one of the extensively applied synthetic GRPR antagonists.…”
Section: Diagnostic Role Of Grpr In Pcamentioning
confidence: 99%
“…GRPR exhibits high expression, especially in early-stage prostate cancers, primarily within tumor cells [ 16 , 41 ]. Radiolabeled GRPR, particularly antagonists, offers precise localization of tumor cell localization, improving therapeutic outcomes.…”
Section: The Role Of Grpr In Prostate Cancer Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that a single injection of 99m Tc‐maSSS‐PEG 2 ‐RM26 was well tolerated after administration. Multiple primary tumors and metastases were effectively visualized by SPECT/CT in both prostate and breast cancers [53, 54].…”
Section: Clinical Applications Of 99mtc‐labeled Peptides For Receptor...mentioning
confidence: 99%